Global burden, trends and health inequalities of stroke attributable to household air pollution, 1990–2021: a decomposition and prediction analysis - Xia, Xiaoqing; Yu, Jing; Suona, Deji; Zhi, Hong; Hao, Yongchen; Wang, Lina (Frontiers in Public Health, 2025)
ObjectiveExposure to household air pollution from solid fuels (HAP) increases stroke risk, affecting approximately 3 billion people worldwide and posing a significant challenge to public health. This study assessed trends in the HAP-related global stroke burden from 1990 to 2021 and quantified associated health inequalities.MethodsData on HAP-attributable stroke disability-adjusted life years (DALYs) and deaths from 1990 to 2021 at global, regional, and national levels were derived from the Global Burden of Disease (GBD) 2021. The estimated annual percentage change (EAPC) was employed to evaluate temporal trends. Decomposition analysis elucidated the primary drivers of burden changes. Cross-country inequality was examined by incorporating the Sociodemographic Index (SDI), and future disease burden was projected.ResultsFrom 1990 to 2021, the age-standardized rates (ASR) of DALYs and deaths from HAP-related stroke declined globally, although significant geographic heterogeneity persisted. Compared with high SDI regions, lower SDI areas bore a heavier burden, with countries such as Zimbabwe and Lesotho experiencing the most notable increases. Furthermore, the share of global ischemic stroke burden increased, whereas intracerebral hemorrhage remained the dominant contributor. Decomposition analysis revealed that population growth consistently served as the main driver of burden increases in low-middle and low SDI areas. Notably, stroke burden was disproportionately concentrated in lower SDI nations, especially for the subarachnoid hemorrhage subtype. Projections suggested that by 2035, the global HAP-related stroke burden would increase, with the ischemic stroke subtype exhibiting the greatest growth.ConclusionAlthough the global HAP-related stroke burden has reduced, significant regional and population disparities persist, along with severe health inequities. Therefore, emphasis should be placed on improving household energy supply and healthcare resource allocation in low-development regions to reduce preventable health inequities.